PENDAPATAN MIGRAN PEKERJA SEKTOR INFORMAL DI PALEMBANG DAN PANGKALPINANG* - Abbas Effendi (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1996)
This research, which was conducted in Palembang and Pangkalpinang in the province of Southern Sumatra, aim at identifying the factors which influence the level if income among permanent migrants in the informal sector. The results of the study indicate that the status of the residential house which is at the same time used as the place of work, has for long, bent over employment, recruitmentof the family labor force, and the level of education is a very dominant factor in the level of income. On the other hand, the variable of the number of workers and the source of capital does not have a dominating influence on the level of income of the migrant workers in the informal sector. Abbas Effendi in this paper argues that the number of workers and the working capital do not constitute major factors in improving on the production or the output, but instead, the factor of effectiveness and efficiency in using the factors of production are crucial in improving on their output.